In praise of shopping temples of Klang Valley - Mohd Azmyl, Md Yusof * (The Malaysian Insight, 2023)
WITH Hari Merdeka and Malaysia Day come and gone, I guess it’s time to get back on the conveyor belts of our modern existence… not.